Comparative Legal Analysis of Reforms Conducted for the Development of the Information Sector in the New Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In this scientific article, the comparative legal analysis of the reforms carried out in the direction of the development of the information sector during the period of President Sh.M.Mirziyoev's power was scientifically analyzed from the legal point of view. It must be recognized that the President of the Republic of Uzbekistan has led a great deal in the development of the information sector, and this process continues today. Many regulatory legal documents have been adopted in the field of regulation of the process of information exchange. Organizations whose task is to develop the industry have started to operate. These aspects are covered in the article. The adopted documents, as well as the significance of the organizations that have started to operate for the development of the industry, have been extensively analyzed from the point of view of legislation. This analysis and presented opinions serve to improve the legislative documents regulating the process of information exchange in our country.